Efektivitas Kebijakan Sertifikasi Guru terhadap Peningkatan Mutu Pembelajaran: Antara Kebutuhan Profesionalisme dan Tuntutan Administratif - Amelia, Rizki; Rozak, Abdul (Media Manajemen Pendidikan, 2025)
The teacher certification policy is one of the government’s key strategies to improve national education quality by strengthening the role of teachers as professionals. Certification is regarded as a continuous professional development instrument that not only enhances teacher capacity but also serves as recognition of the teaching profession. This study aims to analyze the effectiveness of teacher certification in improving learning quality, by examining whether the policy genuinely contributes to teacher professionalism or merely emphasizes administrative compliance. A qualitative descriptive approach was employed through literature review, policy analysis, and limited interviews with teachers and principals. The findings indicate that certification has positive impacts on teacher welfare and formal recognition of the profession, yet it has not significantly contributed to changes in pedagogy or classroom learning quality. Teachers’ motivation tends to be driven by financial incentives rather than professional competence development, while increasing administrative burdens often reduce their focus on teaching. The gap between normative policy objectives and actual practice suggests that certification has not fully functioned as a catalyst for improving learning outcomes. Policy implications highlighted in this study emphasize the need for flexible implementation, including affirmative schemes or special treatment for teachers in disadvantaged regions, to ensure equitable professional development across Indonesia.